2012
DOI: 10.1038/onc.2012.346
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for the pro-oncogenic anterior gradient-2 in cancer development

Abstract: Clinical studies have defined the core 'genetic blueprint' of a cancer cell, but this information does not necessarily predict the cancer phenotype. Signalling hubs that mediate such phenotype have been identified largely using OMICS platforms that measure dynamic molecular changes within the cancer cell landscape. The pro-oncogenic protein anterior gradient 2 (AGR2) is a case in point; AGR2 has been shown using a range of expression platforms to be involved in asthma, inflammatory bowel disease, cell transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
177
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(194 citation statements)
references
References 81 publications
9
177
0
Order By: Relevance
“…AGR2 is highly expressed in numerous human cancers and is associated with the development of various tumor characteristics, including increased proliferation, survival, metastasis, and drug resistance (Brychtova et al 2011;Chevet et al 2013). Increased AGR2 expression has previously been shown to be associated with metastasis and a poor prognosis in breast cancer patients (Barraclough et al 2009), and to correlate with high-grade serous carcinoma and shortened overall survival of ovarian cancer patients (Innes et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AGR2 is highly expressed in numerous human cancers and is associated with the development of various tumor characteristics, including increased proliferation, survival, metastasis, and drug resistance (Brychtova et al 2011;Chevet et al 2013). Increased AGR2 expression has previously been shown to be associated with metastasis and a poor prognosis in breast cancer patients (Barraclough et al 2009), and to correlate with high-grade serous carcinoma and shortened overall survival of ovarian cancer patients (Innes et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since AGR2 is reportedly up-regulated in various types of cancers, its utility as a cancer biomarker and therapeutic target has been investigated by numerous researchers (Brychtova et al 2011;Chevet et al 2013;Salmans et al 2013). Lepreux et al (2011) reported that AGR2 expression was high in normal columnar cholangiocytes and that its expression pattern appeared to be conserved during cholangiocarcinoma development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a member of the protein disulfide isomerase family, AGR2 has a thioredoxin-like domain to aid protein folding and assembly [33,34] and its expression is elevated in the preneoplastic tissue in Barrett's oesophagus and other human cancer cells, where it functions as a proto-oncogene [35][36][37]. AGR2 interacts with multiple proteins including DNA binding proteins and AAA þ ATPase [37][38][39]. The interaction of UNG1 and AGR2 has not been reported before and we propose that the interaction may stabilize UNG1 and enhances its enzymatic activity in DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Agr2 is physiologically localized in endoplasmic reticulum (ER), and it regulates the expression of components of the ER-associated degradation signaling and plays a pivotal role in resistance to ER stress (9)(10)(11). In addition, Agr2 acts as an ER chaperone for the intestinal mucins MUC2, MUC1, and MUC5 (10,12,13).…”
Section: Introductionmentioning
confidence: 99%